Effective Piezo‐Phototronic Enhancement of Flexible Photodetectors Based on 2D Hybrid Perovskite Ferroelectric Single‐Crystalline Thin‐Films. Issue 32 (27th June 2021) - Ding, Ran; Lyu, Yongxin; Wu, Zehan; Guo, Feng; Io, Weng Fu; Pang, Sin‐Yi; Zhao, Yuqian; Mao, Jianfeng; Wong, Man‐Chung; Hao, Jianhua
Abstract: 2D hybrid perovskites are very attractive for optoelectronic applications because of their numerous exceptional properties. The emerging 2D perovskite ferroelectrics, in which are the coupling of spontaneous polarization and piezoelectric effects, as well as photoexcitation and semiconductor behaviors, have great appeal in the field of piezo‐phototronics that enable to effectively improve the performance of optoelectronic devices via modulating the electro‐optical processes. However, current studies on 2D perovskite ferroelectrics focus on bulk ceramics that cannot endure irregular mechanical deformation and limit their application in flexible optoelectronics and piezo‐phototronics. Herein, we synthesize ferroelectric EA4 Pb3 Br10 single‐crystalline thin‐films (SCFs) for integration into flexible photodetectors. The in‐plane multiaxial ferroelectricity is evident within the EA4 Pb3 Br10 SCFs through systematic characterizations. Flexible photodetectors based on EA4 Pb3 Br10 SCFs are achieved with an impressive photodetection performance. More importantly, optoelectronic EA4 Pb3 Br10 SCFs incorporated with in‐plane ferroelectric polarization and effective piezoelectric coefficient show great promise for the observation of piezo‐phototronic effect, which is capable of greatly enhancing the photodetector performance. Under external strains, the responsivity of the flexible photodetectors can be modulated by piezo‐phototronic effect with a remarkable enhancement up to 284%. Our findings shed light on the piezo‐phototronic devices and offer a promising avenue to broaden functionalities of hybrid perovskite ferroelectrics. Abstract : Effective piezo‐phototronic enhancement of flexible photodetectors based on ferroelectric EA4 Pb3 Br10 single‐crystalline thin‐films is demonstrated. Under external strains, the responsivity of the photodetectors can be enhanced by as much as 284%. These findings shed light on the piezo‐phototronic effect for optimizing the performance of perovskite‐based optoelectronic devices, and offer a promising avenue to broaden functionalities of hybrid perovskites.